Microbial quality evaluation of fresh vegetables from distinct markets in urban areas of Bangladesh - Ohiduzzaman; Islam, SM Akramul; Arif, Mohammad; Saddam, Md Jahidul Islam; Uddain, Jasim; Hossain, Muhammad Tofazzal; Kabir, SM Lutful (Asian-Australasian Journal of Food Safety and Security, 2022)
This study was carried out from January to May 2018 to isolate, identify, and determine microbial loads (Staphylococcus aureus; Salmonella; Escherichia coli; Campylobacter) in fresh-marketed vegetables sold at several marketplaces in the districts of Netrokona, Kishoregonj, and Jamalpur. In this study, 90 fresh vegetable samples (carrot, cucumber, coriander leaf, green chili, and tomato) were collected. The spread plate dilution method was utilized for this work, and the organisms were cultivated on selected culture media. Microbes that were expected were discovered utilizing culture and staining procedures. S. aureus, Salmonella, E. coli, and Campylobacter were recovered from all tomatoes (100%), cucumber (100%) and green chili (100%). In carrot samples, the number (%) of S. aureus, E. coli and Campylobacter was 100% except for Salmonella (88.88%). However, 94.44% S. aureus,77.77% Salmonella, 100% E. coli, and 100% Campylobacter were identified in the coriander leaf sample. In conclusion, in salad vegetable samples, high bacterial load and the presence of these organisms, particularly S. aureus, Salmonella, E. coli, and Campylobacter, could serve as an indicator of the need to raise awareness about the potential health hazards caused by improper handling of these vegetables. Asian Australas. J. Food Saf. Secur. 2022, 6 (1), 1-9